Membangun Budaya Akademik yang Beradab dan Beretika di Lingkungan Kampus - Irwansyah; Rini Andriyani; Elza Yusna Nasution (El-Mujtama: Jurnal Pengabdian Masyarakat, 2024)
This research aims to describe the level of academic ethics in building a civilized and ethical academic culture in the campus environment. The method used was quantitative descriptive research with a sample of 30 students at the State Islamic University of Sumatra. Data was collected through a questionnaire that covers various aspects regarding perceptions, understanding and experiences related to academic ethics. The research results show that the majority of respondents, especially women and those from the 19 year age group, consider academic ethics to be very important in the learning process in the classroom. However, there are still challenges in the form of unethical behavior such as plagiarism and lack of student awareness. The campus environment is positively supported in efforts to build a civilized and ethical academic culture, although improvements are still needed in the implementation of related policies and education. In conclusion, this research provides a comprehensive picture of the condition of academic ethics in the campus environment, as well as highlighting several obstacles and areas of improvement that need to be considered in strengthening a civilized and ethical academic culture in the future.